PO011 Therapeutic plasma exchange for neurological disorders: experience at a tertiary neuroscience centre. (1st December 2017) - Das, Joyutpal; Tan, Maevis; Matthews, Rachael; Lilleker, James; Gosal, David; Sharaf, Nazar
Abstract : Therapeutic plasma exchange (TPE) is often used to treat confirmed or suspected immune-mediated neurological disorders. Our experience with TPE at a tertiary neurosciences centre is reported. In this retrospective study, we reviewed the medical records of all 63 patients receiving TPE at the Greater Manchester Neuroscience Centre between 2012–2015. During one procedure, 1–1.5 plasma volumes were removed and replaced with isotonic 4.5% human albumin solution. A typical therapeutic cycle was consisted with 5 procedures within 14 days. A total of 349 procedures were performed during 70 therapeutic cycles. Anti-VGKC antibodies-mediated disorders (n=11), chronic inflammatory demyelinating polyneuropathy (10) and multiple sclerosis (9) were the three commonest indications for TPE. It was used as the first-line treatment in 6% of patients, whilst in 75% it was the second-line therapy. Majority of patients (89%) following TPE required further immunosuppression. 75% of patients had a favourable clinical outcome with TPE. The adverse event rate was 8.6 per hundred treatment cycles (bleeding=1, central line infection=2, venous thromboembolism=3). TPE is being used commonly for the treatment of immune-mediated neurological disorders and is associated with a low adverse event rate. Overall, we observed favourable clinical outcomes following TPE.